An evaluation of oxidative stress and antioxidant capacity in patients with myofascial pain syndrome. Issue 6 (November 2014) - Koca, İrfan; Tutoglu, Ahmet; Boyacı, Ahmet; Pehlivan, Yavuz; Yıldız, Hamit; Turkbeyler, Ibrahim; Sarıcicek, Edibe; Taysi, Seyithan; Onat, Ahmet Mesut
Abstract Objective. To evaluate total antioxidant capacity (TAC) and total oxidative stress (TOS) values in patients with myofascial pain syndrome (MPS). Method. The study comprised 38 patients diagnosed with MPS and 30 healthy volunteers. The age, body mass index (BMI) and pain scores (evaluation by visual analogue scales) of all the participants were recorded. The TAC, TOS and oxidative stress index (OSI) levels were compared between the MPS and control groups. Results. There was no significant difference between the MPS and control groups in respect of demographic characteristics. The TAC levels were determined to be significantly lower and TOS levels and OSI values, significantly higher in the MPS patients than in the control group. Conclusion. The results of this study determined that the oxidant/antioxidant balance was impaired in MPS patients and thus MPS can be considered to be related to an increase in oxidative stress.